Molecular Targets, Population Outcomes: A Biochemical Bridge between Drug Discovery and Community Medicine - Ain-Ul Momina, Nadeem Akhtar Korai, Rafiq Ahmed Siddiqui, Asma Ali, Usman Saeed, Mubasher Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim of Study: This study aims to investigate the translational pathway from identifying molecular drug targets to achieving measurable improvements in community health outcomes, using a multidisciplinary framework integrating pharmacology, biochemistry, and community medicine principles. Study Duration: March 2022 to March 2023. Study Place: Gambat Medical College, Gambat, Niazi Medical & Dental College, Sargodha. Methodology: A mixed-methods approach was employed, comprising: 1) A systematic review of novel drug approvals (2020-2024) to classify molecular targets and therapeutic areas; 2) Quantitative analysis of anonymized local pharmacoepidemiological data from the Niazi Medical College catchment area to assess drug utilization patterns and therapeutic outcomes for chronic diseases; 3) Qualitative focus group discussions with community healthcare workers to identify barriers to effective medication adherence and access; and 4) In silico molecular docking studies on a select target (SARS-CoV-2 Main Protease) to demonstrate the biochemical rationale for drug discovery. Results: The systematic review highlighted a continued focus on kinase inhibitors, monoclonal antibodies, and antiviral agents, with 35% of 2023's novel approvals targeting cancer pathways. Local data revealed suboptimal control rates for hypertension (45%) and type 2 diabetes (38%), with access and adherence cited as major barriers. Molecular docking identified several natural product derivatives with high binding affinity to the SARS-CoV-2 Mpro target. Integrated analysis demonstrated a significant disconnect between the proliferation of targeted therapies and their penetration into primary care formularies for common chronic conditions. Conclusion: A chasm exists between sophisticated molecular drug discovery and real-world community health impact. Bridging this gap requires a deliberate, multidisciplinary strategy encompassing target selection aligned with population disease burdens, drug design informed by pharmacoeconomics and access considerations, and community-engaged implementation science. Future drug development must embed public health outcome metrics from the earliest stages of target identification. Keywords: Molecular Pharmacology, Drug Discovery, Community Medicine, Translational Research, Pharmacoepidemiology, Molecular Docking, Health Outcomes.